La misteriosa travesía, que es "la muerte" (Vida y Ética, 2019)
A medical proposal on death is offered. Death is analyzed as part of life and alien to life, addressing the thinking of various philosophers and the history of medicine. From the medical paradigm brain death is posed, is it a true death? How far can medicine go in its decision about life and death? What is the role of ethics in transplants? And the moral and social problem?It addresses the right to die in a dignified manner and the process of agony. The depersonalization that the agonizing person suffers and the loneliness and fear that it causes in the people who take care of it, in order to face these fears and offer a company in this mysterious and natural process that is absolutely unknown.
Keywords: End; Medium; Dignity; Biomedical Research